Resistive Magnetohydrodynamic Model for Harmonic Expansion of Cylindrical Plasma - K. A. Sargsyan
Analytical model for resistive plasma expansion in a static uniform magnetic field in the regime in which the magnetic field does not perturb the plasma motion is proposed. The model is based on a class of exact solutions for the purely radial expansion of the plasma in the absence of a magnetic field. This approximation permits the reduction of the electromagnetic problem for consideration of a diffusion equation at the external magnetic field. Explicit solutions are derived for resistive cylindrical plasma expanding into a uniform ambient magnetic field. Some numerical examples related to the laserproducedplasma experiments are presented.
Keywords: Physics